Exact solution of stagnation point flow of MHD Cu-H2O nanofluid induced by an exponential stretching sheet with thermal conductivity - Rashid, I; Sagheer, M; Hussain, S (Physica scripta, 2020)
This study presents the stagnation point boundary layer flow of copper-water based nanofluid subject to the applied magnetic field. The flow is caused by the presence of an exponentially stretching porous wall. Heat transfer analysis is also taken into account along with the thermal radiation and Joule heating effects. Mathematical modeling is performed to convert the physical system into a set of mathematical equations which are further simplified by using suitable variables. Exact solutions for the velocity and temperature profiles are computed and interpreted for various physical parameters of interest. It is observed that by increasing the magnitude of the solid volume fraction of nanoparticles, the velocity profile is accelerated. The results also indicate an increment in the Eckert number increases the temperature and the thermal boundary layer thickness.